Biosynthesis of silver nanoparticles from deep sea bacterium Pseudomonas aeruginosa JQ989348 for antimicrobial, antibiofilm, and cytotoxic activity. (18th October 2013) - Ramalingam, V.; Rajaram, R.; PremKumar, C.; Santhanam, P.; Dhinesh, P.; Vinothkumar, S.; Kaleshkumar, K.
<x xml:space="preserve">Abstract</x> Pseudomonas aeruginosa (JQ989348) was isolated from deep sea water sample and used for synthesis of silver nanoparticles (AgNPs). AgNPs were confirmed by analyzing surface plasmon resonance using UV–visible spectrophotometer at 420 nm. Further scanning electron microscope analysis confirmed the range of particle size between 13 and 76 nm and XRD pattern authorizes the anisotropic crystalline nature of AgNPs. Fourier transform infrared spectrum endorsed the presence of high amount of proteins and other secondary metabolites in synthesized AgNPs influence the reduction process and stabilization of nanoparticles. The inhibitory activity of AgNPs was tested against human pathogens showed high activity against Eschericia coli, Vibrio cholerae, Aeromonas sp., and Cornebacterium sp. demonstrating its antimicrobial value against pathogenic diseases. Additionally, biologically synthesized AgNPs have notable anti‐biofilm activity against primary biofilm forming bacteria P. aeruginosa and Staphylococcus aureus. The MTT assay method was evaluated using human cervical cancer cells exposed the AgNPs have excellent cytotoxic activity.